2015
DOI: 10.1093/aob/mcv068
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic structure of the date palm (Phoenix dactylifera) in the Old World reveals a strong differentiation between eastern and western populations

Abstract: This study assesses the distribution and level of genetic diversity of accessible date palm resources, provides new insights on the geographic origins and genetic history of the cultivated component of this species, and confirms the existence of at least two domestication origins. Furthermore, the strong genetic structure clearly established here is a prerequisite for any breeding programme exploiting the effective polymorphism related to each gene pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 53 publications
11
40
0
3
Order By: Relevance
“…In light of recent findings of a strong population division between eastern and western date palm cultivars (Chaluvadi et al 2014;Mathew et al 2015;Zehdi-Azouzi et al 2015;Flowers et al 2019) it is important to consider which geographical regions this allele is found in. All dates with high sucrose shared the same allele that contained the same structure of deletion and this suggests that this Date palm invertase deletion Page nr.…”
Section: Discussionmentioning
confidence: 99%
“…In light of recent findings of a strong population division between eastern and western date palm cultivars (Chaluvadi et al 2014;Mathew et al 2015;Zehdi-Azouzi et al 2015;Flowers et al 2019) it is important to consider which geographical regions this allele is found in. All dates with high sucrose shared the same allele that contained the same structure of deletion and this suggests that this Date palm invertase deletion Page nr.…”
Section: Discussionmentioning
confidence: 99%
“…While we observed it to be more common in North African cultivars, this could simply be a result of multiple cultivars being derived from Deglet Noor. At the same time, despite genomic analysis clearly placing Deglet Noor in the western subpopulation, it has been noted to contain chloroplast DNA from the Eastern subpopulation suggesting Eastern maternal introgression at some point (Zehdi-Azouzi et al, 2015). That it is a derived allele and not ancestral is supported by the fact that we observed related Phoenix species to contain all 3 tandem copies of the invertase genes rather than the deletion.…”
Section: Discussionmentioning
confidence: 56%
“…In light of recent findings of a strong population division between eastern and western date palm cultivars (Chaluvadi, Khanam, Aly, & Bennetzen, 2014;Flowers et al, 2019;Mathew et al, 2015;Zehdi-Azouzi, Cherif, & Moussouni, 2015), it is important to consider which geographical regions this allele is found in. All dates with high sucrose shared the same allele that contained the same structure of West subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic isolation may affect genetic differentiation of some species in certain extent (Bacilieri et al 2013;Zehdi-Azouzi et al 2015). Among the eight natural populations of M. laosensis, the genetic distance between GXFC and GXSS population was the smallest (0.3334), while the genetic distance between GXRX and YNML was the largest (0.7126).…”
Section: Cluster Analysismentioning
confidence: 99%